Analisis SWOT sebagai Penentu Strategi Persaingan pada UMKM Banana Crunchy - Indah Dewi Permata Sari; Alya Aqilla; Zumrotil Auliya; Irghi Edwin Afando (Pusat Riset dan Inovasi Nasional, 2026)
UMKM plays an essential role in Indonesia’s economy but often faces challenges such as intense competition, limited resources, and a rapidly changing business environment. This study aims to analyze the internal and external factors of the UMKM Banana Crunchy using the SWOT analysis approach. The research employs a descriptive qualitative method with data collected through interviews, direct observations, and documentation. The findings show that Banana Crunchy’s main strengths lie in its unique product, favorable taste, and simple production process. Its primary weakness is the less strategic business location. Opportunities arise from the growing trend of modern snacks and the development of digital marketing, while threats come from numerous similar competitors and fluctuations in raw material prices. The recommended strategy is the S–T strategy, which focuses on utilizing product uniqueness to remain competitive.